Pemberdayaan Masyarakat Jombang Berbasis Kewirausahaan Melalui Pendampingan Pembuatan Masker Kain di Masa Pandemi Covid-19 - Wahyuningsih, Roy; Rahayu, Erva Puspita; Maulana, Dimas; Pratiwi, Renata (Jurnal Pengabdian UNDIKMA, 2021)
This community service activity aims to: (1) empower the community by assisting the making of cloth masks for PKK women in Balongbesuk Village, Diwek Jombang. (2) creating entrepreneurial value by producing cloth masks for the market. This activity was carried out for 7 meetings using three main methods, namely program socialization, provision of materials, training and mentoring. This research involved 15 PKK mothers in Balongbesuk Diwek Jombang Village. The results of this assistance to community service activities are (1) community empowerment goes well because PKK women are enthusiastic about participating in this activity (2) PKK women in Balongbesuk Diwek Jombang village are able to produce 200 pcs of cloth masks in good categories for their own consumption and the rest to be marketed.